Conceptualizing the Acculturation of a Worker in a Coasian Firm: A Preliminary View - Mohd Kamal, Khairil Annuar (Universiti Malaysia Sarawak, (UNIMAS), 2011)
The term acculturation is often referred to at the societal level. However, what if the situation is in the Firm context? How might acculturation be viewed in a Firm? In this paper I will use the Coasian definition and conceptualization of a Firm to illustrate how acculturation process happens in a firm. I will conceptualize in broad terms how the process of acculturation works in a Coasian firm. This effort represents preliminary, initial steps to model the process of acculturation in a firm1.